Phosphorus speciation in cultivated organic soils revealed by P K‐edge XANES spectroscopy. Issue 3 (7th May 2020) - Schmieder, Frank; Gustafsson, Jon Petter; Klysubun, Wantana; Zehetner, Franz; Riddle, Matthew; Kirchmann, Holger; Bergström, Lars
Abstract: Cultivated organic soils make a significant contribution to phosphorus (P) leaching losses from agricultural land, despite occupying a small proportion of cultivated area. However, less is known about P mobilisation processes and the P forms present in peat soils compared with mineral soils. In this study, P forms and their distribution with depth were investigated in two cultivated Histosol profiles, using a combination of wet chemical extraction and P K‐edge X‐ray absorption near‐edge structure (XANES) spectroscopy. Both profiles had elevated P content in the topsoil, amounting to around 40 mmol kg −1, and P speciation in both profiles was strongly dominated by organic P. Topsoils were particularly rich in organic P (P‐org), with relative proportions of up to 80%. Inorganic P in the profiles was almost exclusively adsorbed to surface reactive aluminium (Al) and iron (Fe) minerals. In one of the pro‐files, small contributions of Ca‐phosphates were detected. A commonly used P saturation index (PSI) based on ammonium‐oxalate extraction indicated a low to moderate risk of P leaching from both profiles. However, the capacity of soil Al and Fe to retain P in organic soils could be reduced by high competition from organic compounds for sorption sites. This is not directly accounted for in PSI and similar indices. Accumulation of P‐org in the topsoil may be attributable by microbial peat decomposition and transformation of mineral fertiliser P by both microbiota and crops. Moreover, high carbon–phosphorus ratio in the surface peat material in both profiles suggests reduced net mineralisation of P‐org in the two soils. However, advancing microbial peat decomposition will eventually lead to complete loss of peat horizons and to mineralisation of P‐org. Hence, P‐org in both profiles represents a huge potentially mobilised P pool.